110k views
2 votes
1. Solve the equation m2 + 6m=-4 using the quadratic formula.

A. m = 5+3
O B. m = 3+V 5
c. m =-3+1 5
D.m=-5+13

User Shari
by
5.6k points

1 Answer

4 votes

Answer:

-3± √5

Explanation:

It is given that,

m² + 6m = -4

Points to remember

Solution of a quadratic equation ax² + bx + c = 0

x = [-b ± v(b² - 4ac)]/2a

To find the solution of given equation

m² + 6m = -4

⇒ m² + 6m + 4 = 0

Here a = 1, b = 6 and c = 4

m = [-b ± v(b² - 4ac)]/2a

= [-6 ± √(6² - 4*1*4)]/2*1

= [-6 ± √(36 - 16)]/2

= [-6 ± √20]/2

= [-6 ± 2√5]/2

= -3± √5

User Calocedrus
by
6.1k points